Research of Spiral Bevel Gear Tooth Surface Modification Technique based on Machining Center - Wang Lei; Cao Xuemei; Deng Xiaozhong; Lei Baozhen (Jixie chuandong)
On the consideration of the existing tooth surface modification technology of spiral bevel gear limited to special milling tooth machine,a kind of tooth surface modification method based on the machining center is put forward. Based on the forming machining method of spiral bevel gear,the pinion tooth surface equation is derived by using the conjugate principle,and the amount of modification is added to discrete points by applying the differential curved surface equation. The digital gear tooth surface of the pinion is obtained by the NURBS surface meshing,which is analyzed with the theoretical tooth surface of the gear. The cutting experiment on machining center is performed on the machining center,and the rolling test experiments show that the tooth contact area and the simulation results mainly agreed. The feasibility of the modification method proposed is verified,which provides the technical support for the spiral bevel gear tooth being processed on machining center and the control of the meshing quality.